Theoretical and methodological approaches to ecological and economic evaluation of property potential use of water economy complex - Yackova, Olga (Skhid, 2013)
Theoretical and methodological approaches to ecological and economic evaluation of property potential use of water economy complex are generalized in the article. Based on existing property evaluation methodologies elaborated a systematic approach to the evaluation of property potential elements in water management area.